The land before time. The complete collection [videorecording (DVD)] - Freudberg, Judy; Geiss, Tony; Krieger, Stu; Spielberg, Steven, 1946-; Lucas, George, 1944-; Kennedy, Kathleen, 1954-; Marshall, Frank (Universal Studios Home Entertainment, 2016)
The original theatrical movie, Land Before Time, launched this beloved franchise with thirteen sequels and now all fourteen films are together in one DVD collection!